Postural orientation, what to expect in youth athletes? A cohort study on data from the Malmö Youth Sport Study - Ryman Augustsson, S.; Nae, J.; Karlsson, M.; Peterson, T.; Wollmer, P.; Ageberg, E. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background Studies investigating postural orientation in uninjured youth athletes are scarce. Understanding how postural orientation during functional performance tests change with age in uninjured athletes has the potential to enhance awareness of changes in performance after injury and to set realistic goals for injured athletes. Thus, the aim of this study was to explore postural orientation during functional tasks at early adolescence, and changes in postural orientation from early to middle adolescence and relate this to sex, type of sport and right leg lean body mass (RLLBM).